22 GP perceptions of the adequacy of community-based care for patients with advanced heart failure in a uk region (NI): a qualitative study. Issue 3 (1st September 2018) - Graham-Wisener, Lisa; Chen, Jingwen Jessica; Gamble, Kathryn; McGlade, Kieran; Doherty, Jennifer; Donnelly, Patrick; Stone, Carol A
Abstract : Introduction: Although there is recognition of the multi-dimensional needs of patients with advanced heart failure (HF) conventional models of care have traditionally been medically focused. It is unknown whether community-based systems and services have improved and adapted to better meet the emotional social functional and medical needs of patients with HF and their families. Aims: To assess the adequacy of community-based services available in Northern Ireland (NI) to meet the multidimensional needs of patients living with New York Heart Association Stage III and IV HF as experienced and perceived by general practitioners (GP). Methods: Semi-structured interviews were conducted with GPs. Interviews were transcribed independently coded and analysed using a six-step thematic analysis approach. Results: 20 semi-structured interviews were conducted. GPs reported managing patients in a 'reactive rather than proactive' way responding only to acute medical needs with hospital admission the default due to lack of community-based services. Care provided by HF specialists was highly regarded but 'access and coordination' were lacking. Conversations regarding current and future care needs were considered important but challenging due to time constraints and prognostic uncertainty. GPs expressed that 'specialist palliative care (SPC) is only a credible option in end stages' related to limited understanding of the scope of SPC and concern that SPC services are cancer-focused. Conclusions: Despite recent evidence for the effectiveness of integrated SPC in improving quality of life for patients with HF health and social care services within NI have not yet adapted to assess and meet these needs.